2013
DOI: 10.1371/journal.pone.0061735
|View full text |Cite
|
Sign up to set email alerts
|

Primary Medication Non-Adherence after Discharge from a General Internal Medicine Service

Abstract: BackgroundMedication non-adherence frequently leads to suboptimal patient outcomes. Primary non-adherence, which occurs when a patient does not fill an initial prescription, is particularly important at the time of hospital discharge because new medications are often being prescribed to treat an illness rather than for prevention.MethodsWe studied older adults consecutively discharged from a general internal medicine service at a large urban teaching hospital to determine the prevalence of primary non-adherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
92
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 15 publications
3
92
0
2
Order By: Relevance
“…Another factor that could affect our results is that all the prescriptions were issued by primary healthcare physicians, while it has been reported that patients seeing specialists have their prescription dispensed to a greater extent than those seeing GPs . It is also important to consider that we assessed primary non‐adherence in general practice, while many studies have reported primary non‐adherence following discharge from hospital, where the proportion of primary non‐adherence tends to be higher . Lastly, many studies define primary non‐adherence as the proportion of all issued prescriptions that are never dispensed, instead of only prescriptions issued to new users, as in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor that could affect our results is that all the prescriptions were issued by primary healthcare physicians, while it has been reported that patients seeing specialists have their prescription dispensed to a greater extent than those seeing GPs . It is also important to consider that we assessed primary non‐adherence in general practice, while many studies have reported primary non‐adherence following discharge from hospital, where the proportion of primary non‐adherence tends to be higher . Lastly, many studies define primary non‐adherence as the proportion of all issued prescriptions that are never dispensed, instead of only prescriptions issued to new users, as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary non-adherence has been extensively researched in the last decades, often using pharmacy dispensing databases (7,8). Although primary non-adherence has been less extensively studied, the prevalence of primary non-adherence has been reported to be between 2.4% and 30.7% (5,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 This frequent use of health care services is mainly due to lack of understanding of a treatment plan, nonadherence to medical therapy, unawareness of CHF symptom exacerbation, and irregular follow-up. [8][9][10][11][12] Lack of coordination and communication between hospitalists and primary care physicians (PCPs) has been documented. 13,14 PCPs too often do not receive discharge summaries, 15 and when they do receive them, the summaries often lack appropriate documentation of medication indication and advice for follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Also, most studies focus on rates of secondary non‐adherence and medications for chronic conditions. There are far fewer data on the rate of primary non‐adherence to new medication changes made during a hospital admission . The aim of this study was to determine the rate of adherence to medications after discharge from acute general medical hospital admission and identify factors that may be associated with non‐adherence.…”
Section: Introductionmentioning
confidence: 99%